Calculation_of_x_for_Stationary

Calculation_of_x_for_Stationary - Calculation of x for...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Calculation of x for Stationary and Nonstationary States of the 1D Harmonic Oscillator A. The Stationary State ( x,t ) The wavefunction for the ground ( v = 0 ) stationary state is i ( x, t ) = exp E v=0 t v=0 ( x ) . - h Note ( x, t = 0 ) = v=0 ( x ) = real function and thus x Next h i E x t = * ( x, t ) x ( x, t ) dx = E v=0 t v=0 ( x ) x v=0 ( x ) exp i v=0 t exp + - . - - h h t =0 h - = x = x 2=0 ( x ) dx . v i i + exp - = But exp E v=0 t E v=0 t 1 . h h So x t= Finally note x t = 0 since x t =0 h - 2 x 0 ( x ) dx = x t =0 . = 0. B. The Nonstationary State ( x,t ) We define the nonstationary state ( x, t ) by the wavefunction ( x, t ) = 1 i i - + - 0 ( x ) exp h E v=0 t 1 ( x ) exp h E v=1t . 2 Note P ( x, t ) for this state is P ( x, t ) = * ( x, t ) ( x, t ) = 1 i i exp E v=0 t v=0 ( x ) + exp E v=1t v=1 ( x ) h h 2 1 i i exp - - h E v=0 t v=0 ( x ) + exp h E v=1t v=1 ( x ) 2 or P ( x, t ) = 1 2 i i exp + - { v=0 ( x ) + 2v=1 ( x ) + ( E v=1 - E v=0 ) t exp h( E v=1 - E v=0 ) t 2 h v=0 ( x ) v=1 ( x ) } . 1 v h To simplify note E v=1 - E v=0 = h since E v = + . 2 Also since exp ( ix ) + exp ( -ix ) = 2cos x , P ( x, t ) becomes . Check normalization 1 1 P ( x, t ) dx = 2 ( x ) dx + 2 ( x ) dx + cos t ( x ) ( x ) dx h -TM - 2 v =0 -* 2 v =1 - 0 1 = 1 1 ( 1) + ( 1) + cos t ( 0 ) = 1 . 2 2 h - Therefore P ( x, t ) dx = 1 is normalized. t Finally, compute x h - from 1 1 2 2 x v=0 ( x ) + 2 x v=1 ( x ) dx + cos t x v=0 ( x ) v=1 ( x ) dx , -* - 2 - h - x t = ( x, t ) dx = xP or x t = cos t x v=0 ( x ) v=1 ( x ) dx . Summary Stationary i ( x, t ) = exp E v=0 t v=0 ( x ) - h P ( x, t ) = 2=0 ( x ) = P ( x, t = 0 ) v x = h - Nonstationary 1 i 1 ( x, t ) = - + - 0 ( x ) exp h E v=0 t 1 ( x ) exp h E v=1t 2 1 P ( x, t ) = 2=0 ( x ) + 2=1 ( x ) + 2cos t 0 ( x ) 1 ( x ) v v 2 x t = cos t h - x 2=0 ( x ) dx = x v v=0 =0 x v=0 ( x ) v=1 ( x ) dx . ...
View Full Document

This note was uploaded on 06/27/2008 for the course CHEM 370 taught by Professor Oldsleepyman during the Fall '08 term at Purdue.

Ask a homework question - tutors are online